Análisis y evaluación del plan de expansión del sistema de subtransmisión, considerando el incremento de la demanda por la incorporación de las cocinas de inducción en la EEASA. perteneciente a la provincia de Tungurahua durante el período 2015-2025 - Chicaiza Morocho, Cristian Xavier (2016)
The current work was developed as a simulation of a plan expansion subtransmission system, taking into account increasing demand for the incorporation of induction cooktops at EEASA, belonging to Tungurahua province, which allows to analyze and evaluate the correct operation of the elements attached to the 69 KV current stage and projected every two years, taking into account the incorporation by stages of the efficient cooking program (ECP). Beginning with the collection of statistical information, which the company has and measurements at the nodo of the substation subtransmission system, obtaining real data that determines the current state and the projected system for the next decade, additionally the flow simulation of power with help of the software "CYMDIST 7.2" was showed....